Various Therapeutic Methods for the Treatment of Medication-Related Osteonecrosis of the Jaw (MRONJ) and Their Limitations: A Narrative Review on New Molecular and Cellular Therapeutic Approaches - Sung-Woon On; Seoung-Won Cho; Soo-Hwan Byun; Byoung-Eun Yang (MDPI AG, 2021)
Medication-related osteonecrosis of the jaw (MRONJ) is one of the most interesting diseases in the field of maxillofacial surgery. In addition to bisphosphonates, the use of antiresorptive and antiangiogenic agents is known to be the leading cause. However, the exact pathogenesis of MRONJ has not been established, and various hypotheses have been proposed, such as oxidative stress-related theory. As a result, a definitive treatment protocol for MRONJ has not been identified, while various therapeutic approaches are applied to manage patients with MRONJ. Although the surgical approach to treat osteomyelitis of the jaw has been proven to be most effective, there are limitations, such as recurrence and delayed healing. Many studies and clinical trials are being conducted to develop another effective therapeutic modality. The use of some materials, including platelet concentrates and bone morphogenetic proteins, showed a positive effect on MRONJ. Among them, teriparatide is currently the most promising material, and it has shown encouraging results when applied to patients with MRONJ. Furthermore, cell therapy using mesenchymal stem cells showed promising results, and it can be the new therapeutic approach for the treatment of MRONJ. This review presents various treatment methods for MRONJ and their limitations while investigating newly developed and researched molecular and cellular therapeutic approaches along with a literature review.